2006
DOI: 10.1681/asn.2006030301
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Increases in Serum Creatinine with Mortality and Length of Hospital Stay after Coronary Angiography

Abstract: The absence of a universally accepted definition of radiocontrast nephropathy (RCN) has hampered efforts to characterize effectively the incidence and the clinical significance of this condition. The objective of this study was to identify a clinically relevant definition of RCN by assessment of the relationships between increases in serum creatinine (Scr) of varying magnitude after coronary angiography and clinical outcomes. An electronic medical database was used to identify all patients who underwent corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
137
2
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 212 publications
(155 citation statements)
references
References 33 publications
9
137
2
7
Order By: Relevance
“…11 Contrast-induced AKI has serious prognostic implications; it is linked to increases in length of hospital stay and to higher rates of in-hospital cardiovascular events, inhospital mortality, and 1-year and 5-year mortality rates. 5,9,[12][13][14] Even relatively small changes in renal function after administration of contrast medium are associated with substantial increases in mortality rates 14 ; this finding suggests that renal insufficiency is a sensitive marker of poor outcomes for patients at risk or perhaps that transient episodes of renal ischemia may produce secondary hemodynamic or vascular changes in other organs. 15 The materials cited in this review include recent guidelines and published reports of clinical trials of contrastinduced AKI and its prevention.…”
Section: Contrast-inducedmentioning
confidence: 99%
“…11 Contrast-induced AKI has serious prognostic implications; it is linked to increases in length of hospital stay and to higher rates of in-hospital cardiovascular events, inhospital mortality, and 1-year and 5-year mortality rates. 5,9,[12][13][14] Even relatively small changes in renal function after administration of contrast medium are associated with substantial increases in mortality rates 14 ; this finding suggests that renal insufficiency is a sensitive marker of poor outcomes for patients at risk or perhaps that transient episodes of renal ischemia may produce secondary hemodynamic or vascular changes in other organs. 15 The materials cited in this review include recent guidelines and published reports of clinical trials of contrastinduced AKI and its prevention.…”
Section: Contrast-inducedmentioning
confidence: 99%
“…T he intravascular administration of iodinated contrast media is a well-recognized cause of acute kidney injury, which in turn, is associated with in-hospital morbidity and mortality (1)(2)(3)(4). Clinical factors that increase the risk for contrast-induced acute kidney injury (CIAKI) include preexistent kidney disease, diabetes mellitus in the setting of underlying renal impairment, advanced congestive heart failure, intravascular volume depletion, administration of large volumes of contrast, and the use of high-osmolal contrast media (1,(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…For instance the recent definition of AKI, considers a 0.3 mg/dl increase of serum creatinine as an evidence of AKI development rather than a 0.5 mg/dl increase (Shah & Mehta, 2006). Weisbord etal showed that only a 0.25-0.3 mg/dl increase in serum creatinine after coronary angiography was accompanied with significant increase of mortality within 30 days of procedure (Weisbord etal., 2006). In another study only a 5% increases of serum creatinine within 12 hours after the contrast exposure had 75% sensitivity and 72% specificity for detecting CIN.…”
Section: Physicochemical Properties and Classification Of Contrast Mementioning
confidence: 99%